A new experimental approach for small-scale dynamic tests on masonry arches aimed at seismic assessment. (16th December 2021) - Castellano, Anna; Elia, Isabella; Fraddosio, Aguinaldo; Olivieri, Carlo; Piccioni, Mario Daniele
This paper considers the dynamics of stone or brick masonry modeled 'a la Heyman'. Current regulations prescribe for such structures to adopt response spectra based on the identification with a harmonic oscillator. Since 1963, Housner observed that the dynamic of structures behaving unilaterally is more correctly described by the rocking motion. This approach enabled lately other scientists to reconstruct response spectra for arches, portals, and more complex structures. In this light, the present paper focuses on response spectra for masonry arches obtained by performing laboratory tests on a shaking table of scale models produced through 3D printing formworks. The difficulty due to the scaling of friction is overcome by special indents at the interfaces of the blocks enforcing no-sliding conditions. The comparisons with numerical solutions represent the first results, being the final goal to obtain a robust experimental method to test scale models of complex masonry structures.